Renovation of Long-term Care Processes in the Home Environment (Journal of Universal Excellence, 2026)
Research Question (RQ): What are the possibilities for the integration of long-term care processes, and what are their implications for the care of older adults in their home environment?Purpose: The purpose is to identify opportunities to improve the quality and effectiveness of long-term care in the home environment through providing person-centred services. The aim is to analyse existing processes performed by formal caregivers. Based on the process inventory and analysis, opportunities for process integration will be created, and a hypothetical evaluation of the efficiency of the new process will be made.Method: An inventory of processes was taken, and a proposal for an integrated long-term care process model was developed using the eEPC approach to process modelling.Results: An inventory of home help and community health care processes was developed. A proposal for an integrated process of long-term care for people in their home environment was drafted, including some important orientations of the new law in the field of long-term care in Slovenia. With the integration of the processes, there has been a decrease in the number of initial and final events and events in the process, the number of activities and decisions. The evaluation of the financial impact of the integration of care processes is estimated based on a hypothetical case. The cost of care would decrease by almost 20% and the number of working hours of formal providers would decrease by 7 hours per month.Organization: By integrating care services in the home environment and process renovation, it is possible to achieve higher quality of services, optimization of human resources, and greater cost efficiency.Society: With a systematical approach to the research of care processes, integration, and optimization, it is possible to provide high-quality and continuous care that supports the independence of individuals in caring for themselves. This can have a positive impact on the quality of life of care recipients and their lay caregivers. This may also have a positive impact on social spending.Originality: To the best our knowledge, no inventory of community health nursing or home care processes has been conducted yet. With the implementation of the Long Term Care Act in home settings in Slovenia, the proposal for the care process will be able to be verified and may be improved in the future.Limitations/Future Research: The model has not been tested in practice. Its testing and use may reveal the shortcomings of the process model. Its continuous improvement, based in part on the exploration of individual elements of the process model, will ensure the long-term success of the model. It will also be useful to explore the actual financial and other implications of the proposed process model through structural indicators of the effectiveness of process renovation.
Keywords: long-term care; older adults; home care; community health care; process renovation; integration